2016
DOI: 10.1111/jopr.12527
|View full text |Cite
|
Sign up to set email alerts
|

Digital Versus Conventional Impressions in Fixed Prosthodontics: A Review

Abstract: Digital impression techniques are a clinically acceptable alternative to conventional impression methods in fabrication of crowns and short FDPs. For fabrication of implant-supported crowns and FDPs, digital impression systems also result in clinically acceptable fit. Digital impression techniques are faster and can shorten the operation time. Based on this study, the conventional impression technique is still recommended for full-arch impressions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
333
0
15

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 358 publications
(358 citation statements)
references
References 18 publications
10
333
0
15
Order By: Relevance
“…13 Also, several in vitro studies and reviews reported that the marginal and internal fit of 1 to 4 unit restorations obtained by optical impressions were comparable with those obtained by conventional impressions. 11,1419 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Also, several in vitro studies and reviews reported that the marginal and internal fit of 1 to 4 unit restorations obtained by optical impressions were comparable with those obtained by conventional impressions. 11,1419 …”
Section: Discussionmentioning
confidence: 99%
“…9–19 This methodology evaluates the accuracy of the entire fabrication chain and not just the impression system. This fabrication chain includes many error prone steps beginning with optical scanning and the associated 3D model creation processes through all the stages of restoration fabrication (milling, 3D printing, casting) and postfabrication procedures (sintering, finishing, and polishing).…”
mentioning
confidence: 99%
“…Equipped dentists are now using 3 rd generation optical cameras, yet conventional impression techniques are still being employed. The materials required for the latter technique have not followed the vast and rapid evolution of the optical cameras 4. Though still a little-known technique from just a few years ago, optical impression has quickly evolved and offers solutions for larger volume registration in different domains (prosthetics, implantology, orthodontics) 2…”
Section: Introductionmentioning
confidence: 99%
“…Recently newer digital impression systems have proven to be more accurate for not only smaller cases but also larger and more complex cases when compared to conventional elastomeric impressions . Furthermore, digital impressions can be faster and shorten operation time compared to conventional elastomeric impression materials . In a double blind randomized clinical trial, direct digital impressions generated better fitting restorations compared to other traditional impression techniques .…”
Section: Introductionmentioning
confidence: 99%
“…In a double blind randomized clinical trial, direct digital impressions generated better fitting restorations compared to other traditional impression techniques . Consequently, as digital impressions become more ubiquitous, accurate, and user friendly, their use is expanding to include larger and more complex clinical cases …”
Section: Introductionmentioning
confidence: 99%